Tradition and Modernity: the Role of NU in Cultural Transformation in the 2nd Century - Ahmad Suhendra; Nasih Burhani; Indrawan Cahyadi; Ahmad Yunani; Muhammad Dachlan (Nizham Jurnal Studi Keislaman, 2025)
This article examines the role of Nahdlatul Ulama (NU) in maintaining and transforming religious and social culture in Indonesia in the modern era. Using a qualitative approach with literature study methods, in-depth interviews, and discourse analysis, this study explores the expectations of the people towards NU as an institution that must be able to bridge tradition with modernity. The findings show that the people expect NU to maintain religious values and local wisdom while accommodating global dynamics and technological developments. The implications of this study highlight the need for innovative strategies in tradition management, religious education reform, and openness to cross-cultural dialogue to meet the challenges of the second century. In the context of preserving traditions, religious values and local wisdom are the foundation of identity that must be maintained. NU, through educational institutions, da'wah programs, and media management, plays an important role in transmitting cultural heritage to the younger generation.